High-Density Lipoprotein Cholesterol Concentrations and Particle Size Are Modified by Dietary Zinc in Men - Shenvi, Swapna; Chen, Kevin; Kim, Elijah; Zyba, Sarah; King, Sarah; Shigenaga, Mark; Killilea, David; Holland, Tai; Sutherland, Barbara; Krauss, Ronald; King, Janet C. (2017)
Objective To measure biomarkers of lipid metabolism in response to a marginal zinc depletion, repletion, and supplementation in healthy male subjects. Methods Eighteen male subjects between ages of 18–45 consumed a controlled diet (80% carbohydrate, 10% fat, 10% protein) with two levels of dietary zinc. Phase I: Low zinc: 6 mg/day with 1.5 mg of phytate (2 weeks); Phase II: Zinc repletion: 10 mg/day with no phytate (4 weeks). Thereafter, a 25 mg/day zinc supplement was administered with an ad libitum diet for 3 weeks (Phase III). Targeted analysis of lipids and lipoprotein particle size were performed using standard methodology. Results Plasma zinc levels remained unchanged during Phases I and II in all subjects; they increased by 17.4 ± 3.8% (mean ± SE) at the end of supplementation (phase III). Apo-A1 decreased significantly from 119.2 ± 13.2 mg/dL (mean ± SD) to 110.2 ± 13.2 mg/dL (p=0.003) at the end of the low zinc period. Apo-A1 remained low at the end of phase II, but returned back to baseline after supplementation. A similar pattern was observed in HDL-c and HDL-L (large buoyant HDL particles) levels across the three phases. Plasma triglyceride levels increased during the 6-week high-carbohydrate diet, but were not modified by shifts in dietary zinc. Based on our previous observation of higher DNA strand breaks in the low zinc metabolic period and literature reports linking cancer to low HDL-c levels, we performed a correlation analysis of DNA strand breaks and HDL subspecies. Our results show that the percent changes in HDL-L and DNA strand breaks from phase I to II are negatively correlated (r=−0.45; p=0.05). Conclusion Results from our studies show that low zinc combined with a high carbohydrate diet increased biomarkers of dyslipidemia, but provision of adequate dietary zinc or a zinc supplement for a short period of time mitigated the increase in these biomarkers. Support or Funding Information Harvest Plus